Marine Debris on Small Islands: Insights from an Educational Outreach Program in the Spermonde Archipelago, Indonesia - Sur, Christine; Abbott, Jessica M.; Ambo-Rappe, Rohani; Asriani, Nenni; Hameed, Sarah O.; Jellison, Brittany M.; Lestari, Hasriani A.; Limbong, Steven R.; Mandasari, Musdalifah; Ng, Gabriel; Satterthwaite, Erin V.; Syahid, Sulham; et al. (Frontiers in Marine Science, 2018)
Marine debris is a global environmental problem especially apparent on small islands throughout the world. We implemented an educational outreach program to engage primary and secondary students in the scientific process using the tangible issue of marine debris on a typical small island in Indonesia (Barrang Lompo, Spermonde Islands, South Sulawesi). Over a three-year period, students conducted systematic sampling of debris on their island's beaches. They quantified the enormity of the debris problem, discussed data, and compared experiences with partner schools in California. The program inspired a unique, local perspective on marine debris that includes greater awareness of human health impacts as well as a need for realistic solutions to this problem faced by small islands.